Ecological Determinants of Foraging and Caching Behaviour in Sympatric Heteromyid Rodents - Leaver, Lisa (My University, 2000)
A series of studies was carried out in order to ascertain some of the ecological determinants of the foraging and caching behaviour of heteromyid rodents (kangaroo rats, Dipodomys, and pocket mice, Chaetodipus). The results show that heteromyids are sensitive to cues of predation while they are foraging. They put more effort into foraging under the safety of cover and in the dark of the new moon, when risk of predation from visually hunting predators is low. They also modulate their selectivity in relation to cues of predation risk, requiring a better pay-off(a more valuable food) as risk increases. The kangaroo rats and pocket mice compete for resources, and the pocket mice are at an aggressive disadvantage to the kangaroo rats at primary resource patches. However, the pocket mice compensate at least partially for their loss by engaging in cache pilferage. Finally, a study of the scatter caching decisions made by kangaroo rats demonstrates that they adaptively modulate cache spacing by placing more valuable seeds into caches that are more widely spaGed. This differential spacing leads to decreased probability that pilferers conducting area-localised search after encountering one cache will be able to locate further caches. The results are discussed in relation to current theory and empirical findings.
Determinants of Foraging and Caching in Heteromyids
Keywords: foraging; caching; sympatric; heteromyid rodents